Contribuição ao estudo da máquina assíncrona trifásica duplamente alimentada aplicada a aerogeradores de velocidade variável - Costa, Jean Patric da (2006)
This work presents the analysis and implementation of a vector control applied to Doubly-Fed Induction Generators (DFIG) used in grid connected wind turbines. DFIG s are nowadays the more widely used concept for grid connected wind turbine, especially for rated power above 1 MW. The main reason is the low rotor PWM power converter rating. The present work deals with the controller analysis of the back-to-back converter in the stator flux vector reference frame. This method allows a decoupled control of the active and reactive stator power. The PI controller bandwidth analysis in the DFIG dynamic behavior is presented. Initially, the impact of the bandwidth variation of the closed loop rotor current controller and the stability including the PLL estimator are investigated. In addition, this work proposes a new synchronization method that automatically synchronizes the induced stator voltage vector with the grid voltage vector without being affected by the position of the rotor. In order to validate the carried out analysis, experimental results are presented using a 5kW DFIG. It is basically composed by: one DFIG, two power converters connected in the rotor-side and in the grid-side, a line filter and the data acquisition and control system (DSP TMS320F2812). Both converters are commercial units and are vector controlled using appropriate interfaces and they are connected back-to-back, sharing the same DC bus. One of them is supplied through a line filter from the power grid and the other one with the output of the generators rotor. The stator of the generator is directly connected to the power grid. All components are extensively described in the work and their functions are discussed. The control structures for both inverters are presented.